2021
DOI: 10.3390/foods10123100
|View full text |Cite
|
Sign up to set email alerts
|

Marine Health-Promoting Compounds: Recent Trends for Their Characterization and Human Applications

Abstract: Seaweeds represent a rich source of biologically active compounds with several applications, especially in the food, cosmetics, and medical fields. The beneficial effects of marine compounds on health have been increasingly explored, making them an excellent choice for the design of functional foods. When studying marine compounds, several aspects must be considered: extraction, identification and quantification methods, purification steps, and processes to increase their stability. Advanced green techniques h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 176 publications
(447 reference statements)
1
24
0
Order By: Relevance
“…However, due to the cost of enzymes, lack of substrate-specific enzymes, and limitations in maintaining bioreactor conditions, using an appropriate extraction method is required [127,128]. Several experiments have been carried out to identify the structural characteristics of purified phlorotannins, but the drawback is that there is no available library for comparison with the standard [129,130]. The spectrophotometer-based methods, such as the Folin-Ciocâlteu assay, FRAP assay, and ORAC assay, have a low specificity because non-phenolic substances are prone to overestimate the results [131,132].…”
Section: Limitations Related To the Phlorotannin Isolation Purificati...mentioning
confidence: 99%
“…However, due to the cost of enzymes, lack of substrate-specific enzymes, and limitations in maintaining bioreactor conditions, using an appropriate extraction method is required [127,128]. Several experiments have been carried out to identify the structural characteristics of purified phlorotannins, but the drawback is that there is no available library for comparison with the standard [129,130]. The spectrophotometer-based methods, such as the Folin-Ciocâlteu assay, FRAP assay, and ORAC assay, have a low specificity because non-phenolic substances are prone to overestimate the results [131,132].…”
Section: Limitations Related To the Phlorotannin Isolation Purificati...mentioning
confidence: 99%
“…1 ). The chemical composition of S. ilicifolium CE indicated the mannitol as a major bioactive compound, which, according to literature, actively participates in the wound healing process in injured tissues by increasing the viability of collagen fibrils and preventing further cell damage [ 44 ]. Moreover, mannitol is able to modulate wound cell function by enhancing the proliferation and migration of fibroblast cells [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…They act as antioxidants without interfering with the cytotoxic, pro-oxidant anticancer drugs [ 80 ]. Different studies have indicated that the antioxidant effect of carotenoids depends on their structure, location, or site of action [ 81 ]. The chemical structure of some carotenoids with pro-apoptotic activity is shown in Figure 4 , and their possible mechanism of action is in Figure 5 .…”
Section: Pro-apoptotic Activity Of Bioactive Compounds From Seaweedsmentioning
confidence: 99%
“…Fucoxanthin ( B ), a xanthophyll with an allenic bond and 5,6-monoepoxide, is one of the most abundant carotenoids, contributing to more than 10% of the estimated total carotenoid production in nature [ 82 , 83 ]. It has antioxidant, anticancer, antiobesity, and antidiabetic properties [ 81 ]. NF-κB is a protein complex that controls DNA transcription, and its activation generates cell survival, promoting cancer cell growth and inhibiting apoptosis [ 46 ].…”
Section: Pro-apoptotic Activity Of Bioactive Compounds From Seaweedsmentioning
confidence: 99%